The Art of Lamentation between Originality and Renewal in Nigerian Arabic Poetry - Masama, Abubakar Adamu; Rabih, Dayyib Zayid (Journal of Arabic Language Sciences and Literature, 2022)
Lamentation is one of the prominent topics in the ancient Nigerian Arabic poetry, which existed in Nigeria before the twentieth century AD, and that the poet Ibrahim Jalo Muhammad Jalingo is one of the stallions of contemporary Nigerian Arabic poetry and its great poles, and he is among those who success in the field of renewal in the poetry of Nigerian Arabic Elegy, from this point of view This research is an analytical literary study that aims to shed light on images of the trends of renewal and development in the elegies of the Nigerian poet Ibrahim Jalo Muhammad Jalingo, so the research contains the following elements: - A brief history of the poet’s life. - Pictures of lament poetry in ancient Nigerian Arabic literature. - Pictures from the features of renewal in the elegies of the poet Ibrahim Jalo Muhammad Jalingo. - Conclusion.